History of the Subterranean Connections between Calcutta and Howrah. Issue Volume 172:Issue EH 4(2019:Nov.) (6th November 2019) - Singh, Parashuram; Dewanjee, Biswanath; Gangopadhyay, Kaushik; Dey, Ayanangshu
Abstract : The first metro railway started operation for London's Metropolitan Railway line using steam locomotives and wooden carriages (1863). Though Calcutta got its metro in 1984, its connection with Howrah through an underwater tunnel under river Hooghly was first conceived in 1921. Plans for this was conceived by Sir Harley Dalrymple-Hay and he prepared the blue print of a railway from Calcutta to Howrah with 10 stations over its 10.4 km stretch. Unfortunately, the project was abandoned by the Government of Bengal on financial grounds (1923). Then in 1928, Calcutta Electric Supply Corporation, to cater for increasing power demand on both sides of the river, consulted Sir Dalrymple-Hay to provide a tunnel below the lowest scour-level of the river. It was planned to provide a conduit for electrical cables with inspection facilities and this tunnel was built in 1931. Calcutta's East West Metro Line including the underwater stretch below river Hooghly was re-conceived in 2006 and construction started in 2009. This line now crosses the River Hooghly with rail level at a depth of 19 m below river bed with 13 m of water depth in average tide and its projected daily commuters will be almost one million by year 2035.